2022
DOI: 10.1111/lam.13589
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of Melaleuca alternifolia (tea tree) essential oil against biofilm-forming multidrug-resistant cystic fibrosis-associated Pseudomonas aeruginosa as a single agent and in combination with commonly nebulized antibiotics

Abstract: Significance and Impact of the Study: Infection and colonization with Pseudomonas aeruginosa is generally regarded as unavoidable in the adult cystic fibrosis population, and is a major source of morbidity and mortality. The biofilm-forming capacity of P. aeruginosa is a key feature that confers tolerance to otherwise effective antimicrobials. This study provides in vitro evidence that tea tree oil (TTO) has antibiofilm activity and indicates that TTO has a synergistic interaction with tobramycin against P. ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Por otro lado, algunos aceites esenciales derivados de plantas han sido también centro de atención por la actividad antimicrobiana que presentan. Tal es el caso del aceite esencial de tomillo, empleado en ensayos contra Pseudomonas aeruginosa, donde se puede observar una disminución en la viabilidad del microorganismo y la inhibición en la formación de biopelícula (Haines et al 2022). Los aceites esenciales de perejil, la albahaca y el tomillo causan un aumento en la permeabilidad celular, provocando el escape de los componentes celulares, alteraciones en la pared celular, la perdida de ATP en bacterias como B. cereus, S. aureus, P. aeruginosa, E. coli y Salmonella entérica serovar Typhimurium (AlSheikh et al 2020).…”
Section: Antimicrobianosunclassified
“…Por otro lado, algunos aceites esenciales derivados de plantas han sido también centro de atención por la actividad antimicrobiana que presentan. Tal es el caso del aceite esencial de tomillo, empleado en ensayos contra Pseudomonas aeruginosa, donde se puede observar una disminución en la viabilidad del microorganismo y la inhibición en la formación de biopelícula (Haines et al 2022). Los aceites esenciales de perejil, la albahaca y el tomillo causan un aumento en la permeabilidad celular, provocando el escape de los componentes celulares, alteraciones en la pared celular, la perdida de ATP en bacterias como B. cereus, S. aureus, P. aeruginosa, E. coli y Salmonella entérica serovar Typhimurium (AlSheikh et al 2020).…”
Section: Antimicrobianosunclassified
“…Indeed, most of its antimicrobial properties are generally attributed to terpinen-4-ol (also known as 4-carvomenthenol) [2,13], although it is supposed that TTO antimicrobial mechanism results from complex additive interactions between its different components [11]. Many studies showed that most clinically relevant bacteria are susceptible to low TTO concentrations, confirming its role as an effective bactericidal agent [2,11,14,15]. Antimycotic activities of TTO and its major components were also widely assessed on numerous species [2,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%